Empowering Madrasah Plus Aliyah Darul Ulum Students in Utilizing Waste in to Useful Items - Wakit, Saipul; Indriyani; Nuzleha, Muh.; Santoso, Ari Beni; Handayani, Sri (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Garbage is items thrown away by someone who are considered to be no longer usable. The waste problem must be addressed and anticipated by all elements and stakeholders, because if it is not taken seriously then waste can cause various kinds of problems in the community. This community service activity was carried out at Madarasah Aliyah Darul Ulum in Mumbusari village. Objectively, the main problems faced by partners are 1) Do not understand in the technical details of good and correct waste management, 2) Do not have skills in using waste, 3) There is no product from waste basic materials that has use value and economic value. The methods used are socialization to increase understanding about waste management, workshops on utilizing waste into useful items, discussions, questions and answers as well as providing education, awareness and a caring attitude towards the environment (environmental education). The results of this activity are increased knowledge, skills and products produced by partners that can provide beneficial, artistic and economic value.